2007
DOI: 10.1111/j.1468-1331.2006.01705.x
|View full text |Cite|
|
Sign up to set email alerts
|

Gelatinolytic activity of matrix metalloproteinase‐2 and matrix metalloproteinase‐9 in rat brain after implantation of 9L rat glioma cells

Abstract: The matrix metalloproteinases (MMPs) have come to be highlighted by their close relation to the cell invasion of gliomas. The inhibitors of MMPs have undergone extensive development because of its effectiveness against tumor invasion and angiogenesis. Therefore, a suitable animal model is necessary for searching new MMPs inhibitors against gliomas. In this study, we established an experimental model by implanting 9L glioma cells stereotactically into Fisher344 (F344) rat's brain, and the expression and enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Aberrant MMP-9 expression is also implicated in the glioblastoma angiogenesis process. Low basal MMP-9 expression occurs in normal brain tissue, but high expression levels are induced in glioblastomas, and are linked to increased tumour cell proliferation [29]. We found that parthenolide suppresses both tumour cell-induced angiogenesis and expression of the NF-κB targets, i.e., VEGF and MMP-9, in glioblastoma cells.…”
Section: Discussionmentioning
confidence: 85%
“…Aberrant MMP-9 expression is also implicated in the glioblastoma angiogenesis process. Low basal MMP-9 expression occurs in normal brain tissue, but high expression levels are induced in glioblastomas, and are linked to increased tumour cell proliferation [29]. We found that parthenolide suppresses both tumour cell-induced angiogenesis and expression of the NF-κB targets, i.e., VEGF and MMP-9, in glioblastoma cells.…”
Section: Discussionmentioning
confidence: 85%
“…(2) When MMPs are secreted from tumor cells, the invasion of tumor cells is facilitated by increased intravasation and extravasation through the degradation of the ECM and basement membranes. (3)(4)(5)(6) Zhao et al (7) reported that the expression of MMP-2 and MMP-9 was significantly increased in tumor tissue after implantation of 9L rat glioma cells. Moreover, the MMP proteolytic system may also modulate tumor angiogenesis by modulating the release of biologically active vascular endothelial growth factor (VEGF).…”
mentioning
confidence: 99%
“…Among the MMPs that are commonly associated with the progression of astrocytic tumors are the gelatinases and the membrane MMPs, especially MT1-MMP1. Gelatinases A (MMP-2) and B (MMP-9) are undoubtedly the most well-studied MMPs in CNS tumors, and they have been identified as important factors in the development of high-grade gliomas (Munaut et al 2003;Pagenstecher et al 2001;Zhao, et al, 2007). This observation is directly linked to the invasive nature of these tumors because the expression levels of these gelatinases are generally low in normal brain tissue (Van Meter et al, 2001).…”
Section: Wwwintechopencommentioning
confidence: 99%